Tricresyl phosphate and the aerotoxic syndrome of flight crew members – Current gaps in knowledge. (January 2015) - de Boer, Jacob; Antelo, Angel; van der Veen, Ike; Brandsma, Sicco; Lammertse, Nienke
Abstract: Tricresyl phosphate (TCP), and in particular its tri-ortho substituted isomer (o, o, o-TCP), has been frequently used in aircraft engine oil. Bleed air, provided to the flight deck and cabin can contain traces of TCP. TCP can cause neurotoxic effects in humans. Regularly, airline pilots complain about loss of memory, headaches, dizziness, tunnel vision and other neurotoxic effects. The concentrations of TCP reported in flight deck air (max. ca. 50–100 ng m −3 total TCP) do not exceed provisional toxicity thresholds. These thresholds, however, contain a very high uncertainty and need further underpinning. The many non-detects and relatively low TCP concentrations reported suggest that TCP on its own is not likely to be responsible for the reported health problems of pilots. Specific conditions in air planes and other toxic compounds present in bleed air, whether or not in combination with TCP, may be responsible for the reported neurotoxic syndromes. Sensitivity of individuals seems to be an important factor as well. The clinical signs observed with a selected group of pilots are serious enough to call for further elucidation of this issue.